Improving pediatricians' knowledge and skills in suicide prevention: Opportunities for social work. (September 2019) - Behrman, Gary U; Secrest, Scott; Ballew, Paula; Matthieu, Monica M; Glowinski, Anne L; Scherrer, Jeffrey F
Primary care physicians are key gatekeepers for detecting suicidal intent. However, research indicates training gaps for these providers. Standardized screening for suicide risk in primary care can detect youth with suicidal ideation and prompt a referral to behavioral health care before a suicide attempt. What is needed in adolescent primary care is further training in utilizing standardized mental health screening and employing best practices for suicide prevention. In this study, qualitative research methods were used in surfacing community and medical perspectives regarding skills, knowledge, and values that are needed in pediatric medicine to adequately assess for depression and anxiety. Five focus groups were conducted with pediatric residents, adolescents, parents of adolescents who died by suicide, parents with adolescents in the mental health system, and community mental health professionals. Four themes were identified that illustrate what is needed in pediatric training to lower the risks for adolescent suicide: broken mental health system of care; improving doctor/patient/family communication; alleviating stigma; and early detection and treatment that addresses medications, substance abuse, and recovery resources. The goals of this grant funded study were to analyze the data from these focus groups and compare findings across groups to create modules for Saint Louis University pediatric resident training in suicide prevention. This research project can serve as a springboard for social workers to partner with medical educators in their communities to train primary care physicians for early detection of depression, anxiety, and substance abuse to lower adolescent suicide risks.